Corrigendum to ‘Metal content of settled railway dust: factors affecting iron (Fe) content of dust in railway stations in England and implications for human health exposure assessments’ [Environ. Pollut. 406 (2026) 128643] - Adrian T. Lee; Ayoub Saei; Adam Laycock; Emma Marczylo; Michael Whelan; Helen Crabbe (Environmental Pollution, 2026)

Metal content of settled railway dust: factors affecting iron (Fe) content of dust in railway stations in England and implications for human health exposure assessments - Adrian T. Lee; Ayoub Saei; Adam Laycock; Emma Marczylo; Michael Whelan; Helen Crabbe (Environmental Pollution, 2026)

Trends in fertiliser use and efficiency in the Great Barrier Reef catchment area - Stephen E. Lewis; Cassandra S. James; Zoe T. Bainbridge; Aaron M. Davis; Adam Northey; Emma Lawrence; Rebecca Bartley (Journal of Environmental Management, 2026)

Framing of ultra-processed foods in UK news media (2022–2023) and associations with quoted actors’ interests: a mixed-methods study - Jennie C Parnham; Kiara Chang; Michael Essman; Deb Smith; Mike P Etkind; Maisie McKenzie; Prisha Shah; Milica Vasiljevic; Mark Petticrew; Martin White; Anthony A Laverty; Emma Boyland; et al. (Food Policy, 2026)

Developmental, behavioral, metabolomic, and lipidomic assessment of the insect repellent nootkatone reveals limited sublethal toxicity in developing zebrafish (Danio rerio) - Isaac Konig; Hadley Collins; Amany Sultan; Cole D. English; Christopher L. Souders II; Emma Ivantsova; Victor Hugo Buttrós; Adam D. Point; Denina B.D. Simmons; Christopher J. Martyniuk (Pesticide Biochemistry and Physiology, 2026)

Farmers on the frontline: Extreme weather events, mental health, preparedness and adaptation in an Australian sample - Kylie Rice; Tonelle Handley; Emma Austin; Adam J. Rock; Anthony S. Kiem; Rebecca Patrick; Caryn West; Yumiko Coffey; Alison Kennedy; Kim Usher (Journal of Rural Studies, 2026)

Evolving perspectives on agricultural systems research: Contemporary trends and editorial directions - Jagadish Timsina; Mark van Wijk; Krishna Devkota; Antonius G.T. Schut; Carlos Parra-López; Guillaume Martin; James A. Turner; Emma Stephens; Adam M. Komarek; Simon Fielke; Leonard Rusinamhodzi; Nadine Andrieu; et al. (Agricultural Systems, 2026)

Data Considerations for Estimating Ambient Heat Exposure for Environmental Epidemiological Studies - Emma L. Gause; Talia Feldscher; Zachary Popp; Keith R. Spangler; Sean C. Mueller; Quinn H. Adams; TC Chakraborty; Lucy R. Hutyra; Allison James; Thomas J. Luben; Dany Doiron; Carina J. Gronlund; et al. (Current Environmental Health Reports, 2026)

Correction to: Harvesting Asparagopsis: understanding regrowth and associated community dynamics - Najeen Arabelle Rula; Angela Capper; Adam Smith; Robert D. Kinley; Manoj Kumar; Emma L. Jackson (Journal of Applied Phycology, 2026)

Mineral Stabilization Slows Losses of Peatland Carbon Following Long‐Term Drainage for Agriculture - Katy J. Faulkner; Katerina Georgiou; David A. Coomes; Philippa Ascough; Anna Basford; Rodney G. O. Burton; Romy Copley; Emma Keerberg; Alanie Lapina; Kimber Moreland; Christopher Evans; Ross Morrison; et al. (Global Change Biology, 2026)
Cultivated peatlands are a major CO 2 emission source, but the processes that regulate the decomposition of drained peat are debated, especially as drained peat becomes increasingly shallow. Many cultivated peatlands are underlain by a mineral soil layer. Surface subsidence, oxidation and tillage reduce the peat thickness, which intermixes peat with minerals as peat is lost. A key question is whether this mixing can reduce emissions by making soil organic carbon (SOC) more stable by transforming particulate organic carbon (POC)—which dominates the carbon stock in deep drained peatlands and is readily accessible to microbial decomposers—into mineral‐associated organic carbon (MAOC), which is less accessible to decomposers. To explore this question, we surveyed ten sites across the East Anglian Fens in England, a once extensive (~3900 km 2 ) peatland landscape that has been drained for cultivation since the mid‐seventeenth century. We used variation in cultivation to establish a peat loss gradient to evaluate how topsoil SOC (0–40 cm) and its forms change as peat is lost. As the peat was lost, the soils became rich in minerals (rising from 46% to 88% silt+clay content), resulting in an initial 11‐fold rise in newly‐formed MAOC, but a monotonic decline and near‐total loss of POC. POC turnover times were 3158 ± 62 years, indicative of peat, and POC was always older than MAOC; consequently, microbially‐processed peat along with gradual contributions of recently fixed carbon were sources of MAOC. A four‐month laboratory incubation showed that the MAOC:POC ratio was negatively correlated with respiration. We conclude that long‐term carbon retention via MAOC formation has the potential to reduce carbon loss from degraded, mineral‐mixed peatlands. However, because this MAOC pool is itself vulnerable to loss under continued agricultural drainage, this mechanism is expected to slow rather than halt long‐term soil carbon loss from drained peatlands.

Study protocol for FAXAge: a randomized, controlled clinical trial of fasting and exercise to slow aging in humans - Emma Bundgård Fals; Emilie Caroline Springborg; Adam Bjørnholdt Berthelsen; Jonas Nyeman-Nielsen; Steen Larsen; Morten Scheibye-Knudsen (GeroScience, 2026)
Biomarkers of aging, particularly DNA methylation-based clocks, have shown promise as tools to assess whether interventions may impact the rate of biological aging. Among possible interventions physical exercise has shown protective effects against many age-associated diseases, while time-restricted feeding (TRF) has shown metabolic benefits in preclinical models. The combined effect of exercise and TRF on aging biomarkers remains largely unexplored. In this 52-week four-armed, randomized, controlled trial (clinicaltrials.gov: NCT07207044) 240 healthy adults aged 65 and above will be allocated to four groups: combined cardio and strength training (EXE), TRF, combined EXE and TRF, or control. Participants will undergo assessments at baseline, 3, 6, and 12 months, with follow-ups at 2, 5, and 10 years. The primary outcome measure is Dunedin Pace of Aging DNA methylation age with secondary measures including RNA-sequencing, metabolomics, inflammatory markers, microbiome analysis, cognitive and physical measures. By deeply phenotyping participants, the Fasting And eXercise (FAXAge) study will provide novel insights into whether TRF, EXE, or a combination can slow or reverse biological aging in older adults.

Micromorphology and chemistry of mite domatia: mutualistic trait convergence and variation across eight sympatric north American species - Rosemary A. E. Glos; Abrianna J. Soule; Abigail Rose Adams; Macy Arnett; Josephine Marie Eckman; Quinn Isabella Hane; Avery Marie Logan; Emma Rose Morterud; Dominick J. Noeker; Christopher A. Talbot; William Ugorji; Elizabeth VanOstran; et al. (Symbiosis, 2026)
Mite domatia — small structures on plant leaves that house mutualistic mites — are widespread across plants yet remain relatively understudied. Here we investigate the chemistry and micromorphology of mite domatia across sympatric species of broadleaf deciduous woody species that have convergently evolved tuft-form mite domatia. Specifically, we test whether domatia display similar micromorphological and chemical properties using metabolomics and scanning electron microscopy across multiple independent sympatric lineages. To identify domatia-specific phenotypes, we also compare tissue within domatia to that of nearby leaf tissue on each of the four domatium-bearing species, and test whether species with domatia exhibit reduced chemical defense relative to species that lack domatia using four additional species that lack prominent domatia as a control. We found that domatium-bearing species had significantly lower total phenolic concentrations and lower total defense compound abundance compared to control species, consistent with an evolutionary trade-off between chemical and mutualistic defense. However, within leaves, domatium tissue chemical defense did not differ from surrounding laminar tissue. In contrast, trichome morphology showed clear convergent modification: domatium trichomes were 24–31% longer than trichomes elsewhere on the leaf, a pattern reversed in control species. Together, our findings shed light on the degree of phenotypic convergence in a widespread, ecologically important trait.

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Concatenation, Conflict, and Complexity: Genealogical Heterogeneity Mimics Substitutional Heterogeneity for Nucleotide Model Selection - Jenniffer Roa Lozano; Mahamad Sayab Miya; Emma Turner; Duane McKenna; Richard Adams (Journal of Molecular Evolution, 2026)
Phylogenetic conflict—particularly hidden gene-tree discordance generated by incomplete lineage sorting (ILS)—is pervasive in multilocus and phylogenomic datasets, yet its consequences for nucleotide substitution model selection remain poorly understood. Modern molecular studies increasingly collect and concatenate large sets of independent loci sampled across distant and often poorly characterized regions of the genome, creating significant potential for heterogeneity when analyzed in combination. Here, we examine whether intra-alignment genealogical conflict can influence standard model selection procedures to favor parameter-rich substitution models even when sequences evolve under a simple substitution process. Through a series of in silico case studies, we simulated sequence evolution under the simplest rate-homogeneous Jukes–Cantor (JC69) model and generated concatenated alignments as mosaics of multiple loci, each evolving on its own gene tree drawn under the multispecies coalescent. Conflict was increased by manipulating conditions expected to elevate ILS and gene-tree heterogeneity and embedding progressively more hidden genealogies within alignments while holding total alignment length constant. Despite all data being generated under JC69, model selection frequently favored more complex models, with varying sensitivity depending on the number of taxa, the expected amount of conflict, and the specific selection criterion applied. A dominant pattern was frequent inclusion of among-site rate variation parameters (+ G4 and/or + I), and under extreme conflict, model selection increasingly favored richer substitution models (e.g., SYM, GTR). Broadly, our results showed that hidden conflict can manifest as substitutional and rate heterogeneity, driving selection procedures to compensate with additional parameters in concatenated analyses under high conflict. Broadly, our study contributes to a greater understanding and appreciation of the challenges in modeling molecular evolution in the era of multilocus phylogenetics.

Sequencing of historic specimens helps to clarify the long uncertain species distinction of a rare plant, Adenanthos eyrei E.C.Nelson (Proteaceae) - Benjamin M. Anderson; Emma D. Adams; Brendan J. Lepschi; Katherine M. Taylor; Rachel M. Binks (Conservation Genetics, 2026)

Simulated wildfire smoke particulate matter elicits STING-dependent astrocyte-mediated inflammatory signaling and neurotoxicity - Adam J. Schuller; Abigail M. Bibb; Megan R. Hager; Omar A. Yanouri; Emma J. Smith; Aidan M. Briggs; Luke B. Montrose; Ronald B. Tjalkens (NeuroToxicology, 2026)

Building trust in the integration of artificial intelligence into chemical risk assessment: findings from the 2024 ECETOC workshop - Timothy W. Gant; Alistair Boxall; Daniel Burgwinkel; Maryam Zare Jeddi; Ivo Djidrovski; Steffi Friedrichs; Barry Hardy; Thomas Hartung; Daniela Holland; Andreas Karwath; Anne Kienhuis; Nicole Kleinstreuer; et al. (Archives of Toxicology, 2026)
Artificial Intelligence (AI) is increasingly influencing chemical risk assessment, enabling faster, more comprehensive, and potentially more ethical assessments. The application of AI in chemical risk assessment refers to both generative and predictive algorithms encompassing machine learning, to analyse complex chemical, biological, and environmental data and provide insights into adverse effect potential for humans and ecosystems. AI systems support the prediction of chemical hazards, exposure levels, and adverse effects by learning from experimental results, mechanistic models, and regulatory datasets, thereby enhancing the efficiency of safety evaluations. In October 2024, ECETOC held an international workshop, with experts from academia, industry, and regulatory bodies, to reflect upon the historical challenges in integrating multidimensional omics technologies into chemical regulation and explore the current capabilities and future potential of AI in toxicology and regulatory science. Discussions emphasised that implementation of Findable, Accessible, Interoperable, and Reusable (FAIR) data principles is not just a best practice but rather a prerequisite for building transparent, reliable, and unbiased AI systems. The reliability of AI in producing scientifically valid and socially responsible outcomes depends fundamentally on the availability of FAIR data. However, ensuring trustworthiness also requires robust governance frameworks that go beyond data and human oversight. Critical enablers of responsible AI in chemical risk assessment are rigorous governance, explainability, fit-for-purpose applications, and human oversight. ECETOC supports the development of flexible and iterative frameworks advancing development, validation, transparency, accountability, and trust in AI applications in chemicals regulation.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Genomic characterization of Salmonella enterica serotype Saintpaul isolates from horses - Tirth Uprety; Carrie L. Shaffer; Alan Loynachan; Jennifer Janes; Lynne Cassone; Laura Kennedy; Uneeda Bryant; Rebecca Ruby; Melissa Swan; Beatrice T. Sponseller; Emma Adam; Brian Lubbers; et al. (Veterinary Microbiology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Harvesting Asparagopsis: understanding regrowth and associated community dynamics - Najeen Arabelle Rula; Angela Capper; Adam Smith; Robert D. Kinley; Manoj Kumar; Emma L. Jackson (Journal of Applied Phycology, 2026)
The red seaweed Asparagopsis taxiformis can reduce methane emissions in livestock by over 90%, but its mariculture remains in its infancy and biomass for research and commercial use relies partly on wild populations. Knowledge on the impacts of harvesting A. taxiformis is lacking, emphasising the need for ecological research to guide the development of its sustainable harvesting. This study examined the regrowth potential of A. taxiformis meadows following small-scale harvesting. A harvest experiment testing the methods, handpicking and cutting, was conducted in Gladstone, Queensland, Australia, during the austral winter, with plots monitored over six months. Harvesting immediately affected percent cover and shoot length. Handpicked and cut plots exhibited regrowth within four to five months in terms of cover, which notably exceeded or were slightly above that of control plots. The shoot length of harvested plots paralleled that of control plots and was mainly influenced by seasonality. Control plots exhibited reduced growth at three months, suggesting that harvesting mimicked the seasonal reduction in biomass after the winter peak. This study also demonstrated the importance of vegetative propagation in the regrowth of A. taxiformis . The sessile benthic community in harvested plots underwent temporal shifts similar to those in the control plots, indicating that harvesting did not substantially alter community dynamics. Approximately 19 taxa of mobile fauna were recorded within Asparagopsis meadows, potentially indicating its habitat role. Overall, these findings provide ecological insights into the harvesting impacts on this seaweed, with further studies needed to assess broad-scale and long-term impacts.

A Unified Framework for Trend Uncertainty Assessment in Climate Data Records: Demonstration on Global Mean Sea Level - Kevin Gobron; Roland Hohensinn; Xavier Loizeau; Claire E. Bulgin; Christopher J. Merchant; Emma R. Woolliams; Maurice G. Cox; Wouter Dorigo; Thomas Howard; Mary Langsdale; Adam C. Povey; Michaël Ablain; et al. (Surveys in Geophysics, 2026)

The effect of Asparagopsis oil supplementation level on tissue residues and meat quality of Merino sheep fed high- or low-quality basal diets - Charlotte Adam; Emma Doyle; Jillian Dawson; Frances Cowley; Nigel Tomkins; Lewis Kahn; James Preston; Daniel Korir Sitienei; Matthew Tom Harrison; Benjamin W.B. Holman (Small Ruminant Research, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Navigating challenges in spatio-temporal modelling of Antarctic krill abundance: Addressing zero-inflated data and misaligned covariates - André Victor Ribeiro Amaral; Adam M. Sykulski; Sophie Fielding; Emma Cavan (Spatial Statistics, 2025)

Grazing halos reveal differential ecosystem vulnerabilities in vegetated habitats - Mario Minguito‐Frutos; Rohan Arthur; Jordi Boada; Candela Marco‐Méndez; Matthew P. Adams; Jordi F. Pagès; Xavier Buñuel; Albert Pessarrodona; Xavier Turon; Enric Ballesteros; Laura Tamburello; Simone Farina; et al. (Ecology, 2025)
The dynamic balance between primary production and herbivory is key to the resilience of plant‐dominated ecosystems across the world. However, many vegetated ecosystems are becoming increasingly susceptible to herbivore‐triggered collapses, as this balance is disrupted due to predator declines, increasing nutrients, and other interacting impacts of global change. Yet without accessible, cost‐effective tools to evaluate the production‐consumption relationship, it is difficult to know how close an ecosystem is to imminent overgrazing collapse. Here, we explore the effectiveness of individually formed sea urchin grazing halos as robust indicators of marine habitat vulnerability to overgrazing. Halos are grazed patches of bare rock on macrophyte‐dominated substrates that represent the balance between macrophyte production and per capita herbivore consumption. We measured 1211 halos in 31 locations across the Mediterranean Sea to characterize how plant‐herbivore interactions are mediated by endogenous (i.e., species identity, habitat type, and sea urchin size) and exogenous factors (i.e., environmental factors influencing biotic and abiotic contexts: depth, nutrients, temperature, or protection level). Our results show that halo size was effective in detecting differences in the effect of endogenous and exogenous factors on these interactions. Across locations, halo size was sensitive to differences in (i) species identity, with some species being more impactful than others; (ii) the type of habitat, with some habitats being more vulnerable than others; (iii) protection level, with halo size consistently lower inside marine protected areas; (iv) urchin size, with halo size increasing consistently with herbivore size; (v) nutrient conditions, with halo size increasing as nutrient availability decreased; as well as (vi) depth, with halo size increasing consistently with depth. These results indicate that overgrazing vulnerability is highly contingent on local ecological contexts, which strongly mediate plant‐herbivore interactions. While drivers of ecosystem collapse may be global, the ability of ecosystems to cope is often inherently local. We need locally responsive measures and contextually meaningful solutions to manage ecological integrity in the face of global change. In this context, individually measured grazing halos can be a powerful tool in assessing and managing the resilience of macrophyte ecosystems.

Using low levels of antimicrobials and antiseptics as elicitors for environmental isolates to activate or re-activate antimicrobial producing biosynthetic gene clusters - Amy McLeman; Emma Murphy; Adam P. Roberts (Phytochemistry Letters, 2025)

Farmers’ Indigenous knowledge of insect pollination and non-insect services in cocoa production in Offinso municipal district of Ghana - Daniel Dompreh; Emmanuel Acquah; Kuranchie Emma Pearl; Sevor Dora; Mohammed Adams Latif (Journal of Insect Conservation, 2025)

Embodying the impact of climate change for decision makers using augmented reality (AR): A case study of climate-threatened cultural heritage sites in Western Alaska - Emma L. Verstraete; Sharon Kuo; Natasha Adams; Alexandra J. Zachwieja (Environmental Science & Policy, 2025)

Large cobblestone dams for natural flood management in wide peatland gullies - Adam Ryan Johnston; David Brown; Tim Allott; Salim Goudarzi; Martin Kay; David Milledge; Emma Shuttleworth; Tom Spencer; Martin Evans (Ecological Engineering, 2025)

Correction to: Potential sources of impacts linked to ciliate epibiont occurrence on the macrobenthic invertebrates in the Coringa Mangrove Ecosystem: Preliminary documentation - Appalanaidu Sura; Uma Sankar Panda; Sivasankar Ramakrishnan; Kumaraswami Munnoor; Akhilesh Vijay; Santiago De la Puente; Paul Ragnar Berg; Hans Nicolai Adam; Bhavani Emma Narayanaswamy; Mallavarapu Venkata Ramanamurthy (Environmental Science and Pollution Research, 2025)

Potential sources of impacts linked to ciliate epibiont occurrence on the macrobenthic invertebrates in the Coringa Mangrove Ecosystem: Preliminary documentation - Appalanaidu Sura; Uma Sankar Panda; Sivasankar Ramakrishnan; Kumaraswami Munnoor; Akhilesh Vijay; Santiago De la Puente; Paul Ragnar Berg; Adam Hans Nicolai; Bhavani Emma Narayanaswamy; Mallavarapu Venkata Ramanamurthy (Environmental Science and Pollution Research, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Proteoglycan-4 (PRG4) serum concentration is lower in aged mice, and genetic deficiency impacts survival probability, blood parameters, and bone during aging - Adam P. Tanguay; Nikhil G. Menon; Emma Slavin; Mikayla Moody; Erin McEwen; Gregory D. Jay; Joseph Lorenzo; Jenna M. Bartley; Vanessa M. Scanlon; Alix C. Deymier; Tannin A. Schmidt (GeroScience, 2025)

Dose-response of Asparagopsis extract and diet quality effects enteric methane emissions for sheep fed high-forage diets - Charlotte Adam; Frances C. Cowley; Daniel Korir Sitienei; Nigel Tomkins; Lewis Kahn; James Preston; Emma Doyle (Small Ruminant Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA) - Monita Sharma; Erin Huber; Emma Arnesdotter; Holger P. Behrsing; Adam Bettmann; David Brandwein; Samuel Constant; Rahul Date; Abhay Deshpande; Eric Fabian; Amit Gupta; Robert Gutierrez; et al. (Archives of Toxicology, 2025)
Standard information reporting helps to ensure that assay conditions and data are consistently reported and to facilitate inter-laboratory comparisons. Here, we present recommendations on minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA). The TEER assay is extensively used to evaluate the health of an epithelial/endothelial cell culture model and as an indicator of the potential toxicity of a test substance. This publication is the result of an international collaboration─called the RespTox (Respiratory Toxicity) Collaborative─through which twelve laboratories shared their protocols for assessing the barrier function of respiratory epithelial cells using the TEER assay following exposure to substances. The protocols from each laboratory were reviewed to identify general steps for performing the TEER assay, interlaboratory differences between steps, the rationale for differences, whether these differences impact results or cross-laboratory comparisons between TEER measurements. While the MIRTA recommendations are focused on respiratory epithelial cell systems, these recommendations can be adapted for other cell systems that form barriers. The use of these recommendations will support data transparency and reproducibility, reduce challenges in data interpretation, enable cross-laboratory comparisons, help assess study quality, and facilitate the incorporation of the TEER assay into national and international testing guidance.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Characteristics of maternal antibodies transferred to foals raised through maternal equine rotavirus A vaccination - Lianne G. Eertink; Megan Swope; Tirth Uprety; Chithra Sreenivasan; Allen E. Page; Emma N. Adam; Dan Wang; Feng Li (Veterinary Microbiology, 2024)

High throughput screening of cryoprotective agents for vitrification capabilities - Cameron Sugden; Nima Ahmadkhani; Adam Mayo; Emma Anderson; Oluwatomisin Fagbemi; Robert Donatelli; Peyton Manning; Maxwell Sisson; Alec Snyder; Adam Higgins (Cryobiology, 2024)

Epidemiological investigation of equine rotavirus B outbreaks in horses in central Kentucky - Chithra C. Sreenivasan; Ahsan Naveed; Tirth Uprety; Shalini Soni; Olivia Jacob; Emma Adam; Dan Wang; Feng Li (Veterinary Microbiology, 2024)

Restorative function of offshore longline mussel farms with ecological benefits for commercial crustacean species - Thomas Stamp; Simon J. Pittman; Luke A. Holmes; Adam Rees; Benjamin J. Ciotti; Harry Thatcher; Peter Davies; Alice Hall; Georgia Wells; Anna Olczak; Emma V. Sheehan (Science of The Total Environment, 2024)

Magma recharge at Manam volcano, Papua New Guinea, identified through thermal and SO2 satellite remote sensing of open-vent emissions - Adam S. Cotterill; Emma J. Nicholson; Catherine S. L. Hayer; Christopher R. J. Kilburn (Bulletin of Volcanology, 2024)
Manam is one of the most frequently active volcanoes in Papua New Guinea and is a top contributor to global volcanic volatile emissions due to its persistent open-vent degassing. Here, we present a multi-year time series (2018–2021) of thermal and SO 2 emissions for Manam from satellite remote sensing, which we interpret in the context of open-vent feedback between magma supply, reservoir pressure, and outgassing. We classify the time series into four phases based on the varying SO 2 flux and observe a transient, yet substantial, increase in time-averaged SO 2 flux from background levels of ~ 0.6 to ~ 4.72 kt day −1 between March and July 2019. We also identify a transition from temporally coupled to decoupled gas and thermal emissions during this period which we explain in the context of a magma recharge event that supplied new, volatile-rich magma to the shallow plumbing system beneath Manam. We infer that the arrival of this recharge magma triggered the series of eruptions between August 2018 and March 2019. These explosive events collectively removed 0.18 km 3 of degassed residual magma and signalled the onset of a renewed period of unrest that ultimately culminated in a major eruption on 28 June 2019. We quantify the magnitude of “excess” degassing at Manam after the removal of the inferred residual magma. SO 2 emissions reveal that ~ 0.18 km 3 of magma was supplied, but only ~ 0.08 km 3 was erupted between April 2019 and December 2021. We highlight how multi-parameter remote sensing observations over months to years enable the interpretation of open-vent processes that may be missed by short-duration campaign measurements.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Small molecule therapeutics for neutralising venom toxins – a drug discovery approach - Laura-Oana Albulescu; Adam Westhorpe; Amy Marriott; Rachel H. Clare; Emma Stars; Nada Mosallam; Daniel Chong-Jun-Weng; Ramachandran Gunasekar; Charlotte A. Dawson; Christopher Woodley; Nivya James; Rohit Patel; et al. (Toxicon, 2024)

Neutralizing RGMa with Elezanumab Promotes Cerebroprotection and Recovery in Rabbit Middle Cerebral Artery Occlusion - Peer B. Jacobson; Andrea Mothe; Aharon Levy; Michael Krakovsky; Bradley A. Hooker; Xiaomeng Zhang; Jennifer Mollon; Yulia Mordashova; Mathias Droescher; Sabine Weiss; Stefan Barghorn; Ingeborg Dreher; et al. (Translational Stroke Research, 2024)
Repulsive guidance molecule A (RGMa) is an inhibitor of neuronal growth and survival which is upregulated in the damaged central nervous system following acute spinal cord injury (SCI), traumatic brain injury, acute ischemic stroke (AIS), and other neuropathological conditions. Neutralization of RGMa is neuroprotective and promotes neuroplasticity in several preclinical models of neurodegeneration and injury including multiple sclerosis, AIS, and SCI. Given the limitations of current treatments for AIS due to narrow time windows to intervention (TTI), and restrictive patient selection criteria, there is significant unmet need for therapeutic agents that enable tissue survival and repair following acute ischemic damage for a broader population of stroke patients. In this preclinical study, we evaluated whether elezanumab, a human anti-RGMa monoclonal antibody, could improve neuromotor function and modulate neuroinflammatory cell activation following AIS with delayed intervention times up to 24 h using a rabbit embolic permanent middle cerebral artery occlusion model (pMCAO). In two replicate 28-day pMCAO studies, weekly intravenous infusions of elezanumab, over a range of doses and TTIs of 6 and 24 h after stroke, significantly improved neuromotor function in both pMCAO studies when first administered 6 h after stroke. All elezanumab treatment groups, including the 24 h TTI group, had significantly less neuroinflammation as assessed by microglial and astrocyte activation. The novel mechanism of action and potential for expanding TTI in human AIS make elezanumab distinct from current acute reperfusion therapies, and support evaluation in clinical trials of acute CNS damage to determine optimal dose and TTI in humans. Graphical Abstract A: Ramified/resting astrocytes and microglia in a normal, uninjured rabbit brain. B: Rabbit pMCAO brain illustrating lesion on right side of brain (red), surrounded by penumbra (pink) during acute phase post stroke, with minimal injury to left brain hemisphere. Penumbra characterized by activated astrocytes and microglia (region in crosshair within circle), with upregulation of free and bound RGMa. C: Elezanumab binds to both free and bound RGMa, preventing full activation of astrocytes and microglia. D: Elezanumab is efficacious in rabbit pMCAO with a 4 × larger TTI window vs. tPA (6 vs. 1.5 h, respectively). In human AIS, tPA is approved for a TTI of 3-4.5 h. Elezanumab is currently being evaluated in a clinical Ph2 study of AIS to determine the optimal dose and TTI (NCT04309474).

Waterborne exposure to the antineoplastic 5-fluorouracil alters lipid composition in larval zebrafish (Danio rerio) - Emma Ivantsova; Evelyn E. Henry; Isaac Konig; Cole D. English; Christopher L. Souders; Adam D. Point; Denina B.D. Simmons; Christopher J. Martyniuk (Science of The Total Environment, 2024)

Comparing Transcriptomic Points of Departure to Apical Effect Concentrations For Larval Fathead Minnow Exposed to Chemicals with Four Different Modes Of Action - Kevin Flynn; Michelle Le; Monique Hazemi; Adam Biales; David C. Bencic; Brett R. Blackwell; Kendra Bush; Robert Flick; John X. Hoang; John Martinson; Mackenzie Morshead; Kelvin Santana Rodriguez; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Shipwrecks act as de facto Marine Protected Areas in areas of heavy fishing pressure - Jenny Hickman; Joe Richards; Adam Rees; Emma V. Sheehan (Marine Ecology, 2024)
Ubiquitous, industrial use of bottom‐towed fishing gear since the 1800s has altered marine communities and ecosystem services. Outside of legal protection, only areas inaccessible to trawlers are offered any protection. Shipwrecks present hazards to fishing gear and are rarely subject to trawling pressure. As many have been in situ for >100 years, they offer a baseline of ecological potential when trawling pressure is reduced or removed. Five shipwrecks were surveyed off the Berwickshire coast, some within the Static Gear Reserve and others outside. Video transects were collected of shipwrecks, the surrounding 50 m radius and control locations >150 m from the wreck site. Species identified were assigned a category based on their vulnerability to trawling. The effect of distance from a shipwreck on ecological communities within sites Open and Closed to trawling was investigated. The ecological importance of shipwrecks increased relative to trawling pressure. In Open sites, abundance was 340% greater on Wreck locations than Control. Conversely, within Closed sites, abundance was 149% greater in Control locations than Wreck. In Open sites, shipwreck communities are more similar to those in Closed sites, than to the habitat surrounding the shipwreck. Vulnerable species, mostly large, sessile filter feeders, are almost entirely absent from Open sites, but account for ~28% of the total abundance on shipwrecks in Closed sites. This study offers a quantifiable method to evaluate the ecological contribution of shipwrecks in disturbed areas and suggests their role may warrant further research, and consideration in conservation policy, such as inclusion in 30 × 30 objectives. Our findings also demonstrate the possible ecological gains of expanding or including static gear reserves across Marine Protected Areas.

A gene therapy targeting medium-chain acyl-CoA dehydrogenase (MCAD) did not protect against diabetes-induced cardiac pathology - Kate L. Weeks; Helen Kiriazis; Glenn D. Wadley; Emma I. Masterman; Nicola M. Sergienko; Antonia J. A. Raaijmakers; Adam J. Trewin; Claudia A. Harmawan; Gunes S. Yildiz; Yingying Liu; Brian G. Drew; Paul Gregorevic; et al. (Journal of Molecular Medicine, 2024)

Reproductive biology of male common dolphins (Delphinus delphis) in New Zealand waters - Emily I. Palmer; Emma L. Betty; Sinéad Murphy; Matthew R. Perrott; Adam N. H. Smith; Karen A. Stockin (Marine Biology, 2023)
Reproductive parameters were assessed in 64 male common dolphins ( Delphinus delphis ) examined post-mortem from strandings and bycatch in New Zealand between 1999 and 2020. The stages of male sexual maturation were assessed using morphological measurements and histological examination of testicular tissue. Age was determined via growth layer groups (GLGs) in teeth. The average age (ASM) and length (LSM) at attainment of sexual maturity were estimated to be 8.8 years and 198.3 cm, respectively. Individual variation in ASM (7.5–10 years) and LSM (190–220 cm) was observed in New Zealand common dolphins. However, on average, sexual maturity was attained at a similar length but at a marginally younger age (< 1 year) in New Zealand compared to populations in the Northern Hemisphere. All testicular variables proved better predictors of sexual maturity compared to demographic variables (age and total body length), with combined testes weight the best outright predictor of sexual maturity. Reproductive seasonality was observed in male common dolphins, with a significant increase in combined testes weight in austral summer. This aligns with most other studied populations, where seasonality in reproduction is typically observed. Given the known anthropogenic impacts on New Zealand common dolphins, we recommend that these findings be used as a baseline from which to monitor population-level changes as part of conservation management efforts.

Top ten priorities for global saltmarsh restoration, conservation and ecosystem service research - Julien Pétillon; Emma McKinley; Meghan Alexander; Janine B. Adams; Christine Angelini; Thorsten Balke; John N. Griffin; Tjeerd Bouma; Sally Hacker; Qiang He; Marc J.S. Hensel; Carles Ibáñez; et al. (Science of The Total Environment, 2023)

The Effect of Inhaled Ciclesonide Treatment on Systemic Markers of Immune Function in Horses - Allen E. Page; Mackenzie Johnson; Jordan L. Parker; Olivia Jacob; Melissa Swan; Emma Adam (Journal of Equine Veterinary Science, 2023)

Peatland gully restoration with stone and timber dams (Kinder Plateau, UK) - Tim Howson; Martin Evans; Tim Allott; Emma Shuttleworth; Adam Johnston; Joe Rees; David Milledge; Donald Edokpa; Chris Lockyer; Martin Kay; Tom Spencer; David Brown; et al. (Ecological Engineering, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Effects of High-Speed Training on Messenger RNA Expression in Two-Year-Old Thoroughbred Racehorses - Mackenzie G. Johnson; Emma Adam; Andrew Watt; Allen E. Page (Journal of Equine Veterinary Science, 2023)

Reproductive biology of female common dolphins (Delphinus delphis) in New Zealand waters - Emily I. Palmer; Emma L. Betty; Sinéad Murphy; Matthew R. Perrott; Adam N. H. Smith; Karen A. Stockin (Marine Biology, 2022)
Reproductive biology was assessed in 106 female common dolphins ( Delphinus delphis ) examined post-mortem from stranding and bycatch events along the New Zealand coastline between 1997 and 2019. The average age (ASM) and length (LSM) at sexual maturity was estimated at 7.5 years and 183.5 cm, respectively. The total number of corpora in mature individuals increased with age and appeared to persist throughout life. Ovarian asymmetry was apparent, with the left ovary displaying higher rates of ovulation, and a maximum of 19 corpora recorded for a 24-year-old female. The estimated ovulation and annual pregnancy rates for mature females were 0.39 year −1 and 30%, respectively. Conception and calving occurred year-round, with a weak seasonal increase observed in late austral spring and early austral summer. As these data did not clearly show whether seasonality was present, the gestation, lactation, and resting periods were calculated as either 12.6 or 12.8 months based on the presence/absence of seasonality, respectively. Similarly, calving interval ranged from 3.15 to 3.2 years, depending upon whether seasonality was considered. The estimated LSM of the New Zealand population aligns with other populations globally, although the estimated ASM is younger by approximately 6 months. Other reproductive parameters align with Northern Hemisphere populations, although demonstrate variation, which may reflect adaptations to local conditions such as water temperature and prey availability. As the species is subject to anthropogenic impacts including pollution and bycatch, we suggest our findings be used as a baseline with which to monitor trends in population parameters.

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Mapping risk to plant populations from short fire intervals via relationships between maturation period and environmental productivity - Carl R. Gosper; Ben P. Miller; Rachael V. Gallagher; Janine Kinloch; Richard van Dongen; Emma Adams; Sarah Barrett; Anne Cochrane; Sarah Comer; Lachlan McCaw; Russell G. Miller; Suzanne M. Prober; et al. (Plant Ecology, 2022)

Coastal high-frequency radars in the Mediterranean – Part 2: Applications in support of science priorities and societal needs - Emma Reyes; Eva Aguiar; Michele Bendoni; Maristella Berta; Carlo Brandini; Alejandro Cáceres-Euse; Fulvio Capodici; Vanessa Cardin; Daniela Cianelli; Giuseppe Ciraolo; Lorenzo Corgnati; Vlado Dadić; et al. (Ocean Science, 2022)
The Mediterranean Sea is a prominent climate-change hot spot, with many socioeconomically vital coastal areas being the most vulnerable targets for maritime safety, diverse met-ocean hazards and marine pollution. Providing an unprecedented spatial and temporal resolution at wide coastal areas, high-frequency radars (HFRs) have been steadily gaining recognition as an effective land-based remote sensing technology for continuous monitoring of the surface circulation, increasingly waves and occasionally winds. HFR measurements have boosted the thorough scientific knowledge of coastal processes, also fostering a broad range of applications, which has promoted their integration in coastal ocean observing systems worldwide, with more than half of the European sites located in the Mediterranean coastal areas. In this work, we present a review of existing HFR data multidisciplinary science-based applications in the Mediterranean Sea, primarily focused on meeting end-user and science-driven requirements, addressing regional challenges in three main topics: (i) maritime safety, (ii) extreme hazards and (iii) environmental transport process. Additionally, the HFR observing and monitoring regional capabilities in the Mediterranean coastal areas required to underpin the underlying science and the further development of applications are also analyzed. The outcome of this assessment has allowed us to provide a set of recommendations for future improvement prospects to maximize the contribution to extending science-based HFR products into societally relevant downstream services to support blue growth in the Mediterranean coastal areas, helping to meet the UN's Decade of Ocean Science for Sustainable Development and the EU's Green Deal goals.

Coastal high-frequency radars in the Mediterranean – Part 1: Status of operations and a framework for future development - Pablo Lorente; Eva Aguiar; Michele Bendoni; Maristella Berta; Carlo Brandini; Alejandro Cáceres-Euse; Fulvio Capodici; Daniela Cianelli; Giuseppe Ciraolo; Lorenzo Corgnati; Vlado Dadić; Bartolomeo Doronzo; et al. (Ocean Science, 2022)
Due to the semi-enclosed nature of the Mediterranean Sea, natural disasters and anthropogenic activities impose stronger pressures on its coastal ecosystems than in any other sea of the world. With the aim of responding adequately to science priorities and societal challenges, littoral waters must be effectively monitored with high-frequency radar (HFR) systems. This land-based remote sensing technology can provide, in near-real time, fine-resolution maps of the surface circulation over broad coastal areas, along with reliable directional wave and wind information. The main goal of this work is to showcase the current status of the Mediterranean HFR network and the future roadmap for orchestrated actions. Ongoing collaborative efforts and recent progress of this regional alliance are not only described but also connected with other European initiatives and global frameworks, highlighting the advantages of this cost-effective instrument for the multi-parameter monitoring of the sea state. Coordinated endeavors between HFR operators from different multi-disciplinary institutions are mandatory to reach a mature stage at both national and regional levels, striving to do the following: (i) harmonize deployment and maintenance practices; (ii) standardize data, metadata, and quality control procedures; (iii) centralize data management, visualization, and access platforms; and (iv) develop practical applications of societal benefit that can be used for strategic planning and informed decision-making in the Mediterranean marine environment. Such fit-for-purpose applications can serve for search and rescue operations, safe vessel navigation, tracking of marine pollutants, the monitoring of extreme events, the investigation of transport processes, and the connectivity between offshore waters and coastal ecosystems. Finally, future prospects within the Mediterranean framework are discussed along with a wealth of socioeconomic, technical, and scientific challenges to be faced during the implementation of this integrated HFR regional network.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Mechanisms of breast cancer metastasis - S. David Nathanson; Michael Detmar; Timothy P. Padera; Lucy R. Yates; Danny R. Welch; Thomas C. Beadnell; Adam D. Scheid; Emma D. Wrenn; Kevin Cheung (Clinical & Experimental Metastasis, 2022)
Invasive breast cancer tends to metastasize to lymph nodes and systemic sites. The management of metastasis has evolved by focusing on controlling the growth of the disease in the breast/chest wall, and at metastatic sites, initially by surgery alone, then by a combination of surgery with radiation, and later by adding systemic treatments in the form of chemotherapy, hormone manipulation, targeted therapy, immunotherapy and other treatments aimed at inhibiting the proliferation of cancer cells. It would be valuable for us to know how breast cancer metastasizes; such knowledge would likely encourage the development of therapies that focus on mechanisms of metastasis and might even allow us to avoid toxic therapies that are currently used for this disease. For example, if we had a drug that targeted a gene that is critical for metastasis, we might even be able to cure a vast majority of patients with breast cancer. By bringing together scientists with expertise in molecular aspects of breast cancer metastasis, and those with expertise in the mechanical aspects of metastasis, this paper probes interesting aspects of the metastasis cascade, further enlightening us in our efforts to improve the outcome from breast cancer treatments.

Complete genome of the thermophilic purple sulfur Bacterium Thermochromatium tepidum compared to Allochromatium vinosum and other Chromatiaceae - W. Matthew Sattley; Wesley D. Swingley; Brad M. Burchell; Emma D. Dewey; Mackenzie K. Hayward; Tara L. Renbarger; Kathryn N. Shaffer; Lynn M. Stokes; Sonja A. Gurbani; Catrina M. Kujawa; D. Adam Nuccio; Jacob Schladweiler; et al. (Photosynthesis Research, 2022)

Promoting FAIR Data Through Community-driven Agile Design: the Open Data Commons for Spinal Cord Injury (odc-sci.org) - Abel Torres-Espín; Carlos A. Almeida; Austin Chou; J. Russell Huie; Michael Chiu; Romana Vavrek; Jeff Sacramento; Michael B. Orr; John C. Gensel; Jeffery S. Grethe; Maryann E. Martone; Karim Fouad; et al. (Neuroinformatics, 2022)
The past decade has seen accelerating movement from data protectionism in publishing toward open data sharing to improve reproducibility and translation of biomedical research. Developing data sharing infrastructures to meet these new demands remains a challenge. One model for data sharing involves simply attaching data, irrespective of its type, to publisher websites or general use repositories. However, some argue this creates a ‘data dump’ that does not promote the goals of making data Findable, Accessible, Interoperable and Reusable (FAIR). Specialized data sharing communities offer an alternative model where data are curated by domain experts to make it both open and FAIR. We report on our experiences developing one such data-sharing ecosystem focusing on ‘long-tail’ preclinical data, the Open Data Commons for Spinal Cord Injury (odc-sci.org). ODC-SCI was developed with community-based agile design requirements directly pulled from a series of workshops with multiple stakeholders (researchers, consumers, non-profit funders, governmental agencies, journals, and industry members). ODC-SCI focuses on heterogeneous tabular data collected by preclinical researchers including bio-behaviour, histopathology findings and molecular endpoints. This has led to an example of a specialized neurocommons that is well-embraced by the community it aims to serve. In the present paper, we provide a review of the community-based design template and describe the adoption by the community including a high-level review of current data assets, publicly released datasets, and web analytics. Although odc-sci.org is in its late beta stage of development, it represents a successful example of a specialized data commons that may serve as a model for other fields.

The function‐dominance correlation drives the direction and strength of biodiversity–ecosystem functioning relationships - Michael S. Crawford; Kathryn E. Barry; Adam T. Clark; Caroline E. Farrior; Jes Hines; Emma Ladouceur; Jeremy W. Lichstein; Isabelle Maréchaux; Felix May; Akira S. Mori; Björn Reineking; Lindsay A. Turnbull; et al. (Ecology Letters, 2021)
Community composition is a primary determinant of how biodiversity change influences ecosystem functioning and, therefore, the relationship between biodiversity and ecosystem functioning (BEF). We examine the consequences of community composition across six structurally realistic plant community models. We find that a positive correlation between species’ functioning in monoculture versus their dominance in mixture with regard to a specific function (the “function‐dominance correlation”) generates a positive relationship between realised diversity and ecosystem functioning across species richness treatments. However, because realised diversity declines when few species dominate, a positive function‐dominance correlation generates a negative relationship between realised diversity and ecosystem functioning within species richness treatments. Removing seed inflow strengthens the link between the function–dominance correlation and BEF relationships across species richness treatments but weakens it within them. These results suggest that changes in species’ identities in a local species pool may more strongly affect ecosystem functioning than changes in species richness.

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Correction to: the Cysteine (Cys) Residues Cys-6 and Cys-111 in Mutant Superoxide Dismutase 1 (SOD1) A4V Are Required for Induction of Endoplasmic Reticulum Stress in Amyotrophic Lateral Sclerosis - Emma R. Perri; Sonam Parakh; Marta Vidal; Prachi Mehta; Yi Ma; Adam K. Walker; Julie D. Atkin (Journal of Molecular Neuroscience, 2020)

The Cysteine (Cys) Residues Cys-6 and Cys-111 in Mutant Superoxide Dismutase 1 (SOD1) A4V Are Required for Induction of Endoplasmic Reticulum Stress in Amyotrophic Lateral Sclerosis - Emma R. Perri; Sonam Parakh; Marta Vidal; Prachi Mehta; Yi Ma; Adam K. Walker; Julie D. Atkin (Journal of Molecular Neuroscience, 2020)

Seagrass Restoration Is Possible: Insights and Lessons From Australia and New Zealand - Yi Mei Tan; Oliver Dalby; Gary A. Kendrick; John Statton; Elizabeth A. Sinclair; Matthew W. Fraser; Peter I. Macreadie; Chris L. Gillies; Rhys A. Coleman; Michelle Waycott; Kor-jent van Dijk; Adriana Vergés; et al. (Frontiers in Marine Science, 2020)

Donor hearts in the Sydney Heart Bank: reliable control but is it ‘normal’ heart? - Steven Marston; Adam Jacques; Christopher Bayliss; Emma Dyer; Massimiliano Memo; Maria Papadaki; Andrew Messer (Biophysical Reviews, 2020)
Human heart samples from the Sydney Heart Bank have become a de facto standard against which others can be measured. Crucially, the heart bank contains a lot of donor heart material: for most researchers this is the hardest to obtain and yet is necessary since we can only study the pathological human heart in comparison with a control, preferably a normal heart sample. It is not generally realised how important the control is for human heart studies. We review our studies on donor heart samples. We report the results obtained with 17 different donor samples collected from 1994 to 2011 and measured from 2005 to 2015 by our standard methodology for in vitro motility and troponin I phosphorylation measurements. The donor heart sample parameters are consistent between the hearts, over time and with different operators indicating that Sydney Heart Bank donor hearts are a valid baseline control for comparison with pathological heart samples. We also discuss to what extent donor heart samples are representative of the normal heart.

Fluoxetine effects on behavior and adult hippocampal neurogenesis in female C57BL/6J mice across the estrous cycle - Christine N. Yohn; Sophie Shifman; Alexander Garino; Emma Diethorn; Leshya Bokka; Sandra A. Ashamalla; Benjamin Adam Samuels (Psychopharmacology, 2020)

The tree species matters: Biodiversity and ecosystem service implications of replacing Scots pine production stands with Norway spruce - Adam Felton; Lisa Petersson; Oscar Nilsson; Johanna Witzell; Michelle Cleary; Annika M. Felton; Christer Björkman; Åsa Ode Sang; Mats Jonsell; Emma Holmström; Urban Nilsson; Jonas Rönnberg; et al. (Ambio, 2020)
The choice of tree species used in production forests matters for biodiversity and ecosystem services. In Sweden, damage to young production forests by large browsing herbivores is helping to drive a development where sites traditionally regenerated with Scots pine ( Pinus sylvestris ) are instead being regenerated with Norway spruce ( Picea abies ). We provide a condensed synthesis of the available evidence regarding the likely resultant implications for forest biodiversity and ecosystem services from this change in tree species. Apart from some benefits (e.g. reduced stand-level browsing damage), we identified a range of negative outcomes for biodiversity, production, esthetic and recreational values, as well as increased stand vulnerability to storm, frost, and drought damage, and potentially higher risks of pest and pathogen outbreak. Our results are directly relevant to forest owners and policy-makers seeking information regarding the uncertainties, risks, and trade-offs likely to result from changing the tree species in production forests.

Exploring perceptions of consanguineous unions with women from an East London community: analysis of discussion groups - Meghan A. Cupp; Mary Adams; Michelle Heys; Monica Lakhanpaul; Emma C. Alexander; Yasmin Milner; Tausif Huq; Meradin Peachey; Lakmini Shah; Iram Shazia Mirza; Logan Manikam (Journal of Community Genetics, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Spatiotemporal variations of extreme sea levels around the South China Sea: assessing the influence of tropical cyclones, monsoons and major climate modes - Dat T. Pham; Adam D. Switzer; Gabriel Huerta; Aron J. Meltzner; Huan M. Nguyen; Emma M. Hill (Natural Hazards, 2019)

Sublethal effects of natural parasitism act through maternal, but not paternal, reproductive success in a wild population - Olivia Hicks; Jonathan A. Green; Francis Daunt; Emma J. A. Cunningham; Mark Newell; Adam Butler; Sarah J. Burthe (Ecology, 2019)
Parasites are a major component of all animal populations. Males and females often differ in their levels of parasite prevalence, potentially leading to sex differences in the impact of parasitism on fitness, with important implications for the evolution of parasite and host traits including resistance, tolerance, and virulence. However, quantitative measures of the impact of parasitism under free‐living conditions are extremely rare, as they require detailed host demographic data with measures of parasite burden over time. Here, we use endoscopy for direct quantification of natural‐parasite burdens and relate these to reproductive success over 7 yr in a wild population of seabirds. Contrary to predictions, only female burdens were associated with negative impacts of parasitism on breeding success, despite males having significantly higher burdens. Female reproductive success declined by 30% across the range of natural parasite burdens. These effects persisted when accounting for interannual population differences in breeding success. Our results provide quantitative estimates of profound sub‐lethal effects of parasitism on the population. Importantly, they highlight how parasites act unpredictably to shape ecological and evolutionary processes in different components of the same population, with implications for demography and selection on host and parasite traits.

Evolving and Sustaining Ocean Best Practices and Standards for the Next Decade - Jay Pearlman; Mark Bushnell; Laurent Coppola; Johannes Karstensen; Pier Luigi Buttigieg; Francoise Pearlman; Pauline Simpson; Michele Barbier; Frank E. Muller-Karger; Cristian Munoz-Mas; Peter Pissierssens; Cyndy Chandler; et al. (Frontiers in Marine Science, 2019)

Consequences for bird diversity from a decrease in a foundation species—replacing Scots pine stands with Norway spruce in southern Sweden - Matts Lindbladh; Lisa Petersson; Per-Ola Hedwall; Renats Trubins; Emma Holmström; Adam Felton (Regional Environmental Change, 2019)

Application of GNSS interferometric reflectometry for detecting storm surges - Dongju Peng; Emma M. Hill; Linlin Li; Adam D. Switzer; Kristine M. Larson (GPS Solutions, 2019)

Computational Tracking of Shear-Mediated Platelet Interactions with von Willebrand Factor - Adam Ralph; Martin Somers; Jonathan Cowman; Bruno Voisin; Emma Hogan; Hannah Dunne; Eimear Dunne; Barry Byrne; Nigel Kent; Antonio J. Ricco; Dermot Kenny; Simon Wong (Cardiovascular Engineering and Technology, 2016)

Replacing monocultures with mixed-species stands: Ecosystem service implications of two production forest alternatives in Sweden - Adam Felton; Urban Nilsson; Johan Sonesson; Annika M. Felton; Jean-Michel Roberge; Thomas Ranius; Martin Ahlström; Johan Bergh; Christer Björkman; Johanna Boberg; Lars Drössler; Nils Fahlvik; et al. (Ambio, 2016)

Environmental manipulation of growth and energy carrier release from freshwater and marine Chlamydomonas species - Tyson A. Burch; William W. Adams; Benoît L. S. Degrenne; Calvin H. Englert; Brita R. Mines; Parker C. Nash; Emma C. Boone; Barbara Demmig-Adams (Journal of Applied Phycology, 2015)

Understanding urinary conditioning film components on ureteral stents: profiling protein components and evaluating their role in bacterial colonization - Chelsea N. Elwood; Joey Lo; Emily Chou; Adam Crowe; Olga Arsovska; Hans Adomat; Ricardo Miyaoka; Emma Tomlinson-Guns; Manoj Monga; Ben H. Chew; Dirk Lange (Biofouling, 2013)

Sequencing wheat chromosome arm 7BS delimits the 7BS/4AL translocation and reveals homoeologous gene conservation - Paul J. Berkman; Adam Skarshewski; Sahana Manoli; Michał T. Lorenc; Jiri Stiller; Lars Smits; Kaitao Lai; Emma Campbell; Marie Kubaláková; Hana Šimková; Jacqueline Batley; Jaroslav Doležel; et al. (Theoretical and Applied Genetics, 2012)

Impulsive behaviour induced by both NMDA receptor antagonism and GABAA receptor activation in rat ventromedial prefrontal cortex - Emily R. Murphy; Anushka B. P. Fernando; Gonzalo P. Urcelay; Emma S. J. Robinson; Adam C. Mar; David E. H. Theobald; Jeffrey W. Dalley; Trevor W. Robbins (Psychopharmacology, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Dissociable effects of noradrenaline, dopamine, and serotonin uptake blockade on stop task performance in rats - Andrea Bari; Dawn M. Eagle; Adam C. Mar; Emma S. J. Robinson; Trevor W. Robbins (Psychopharmacology, 2009)

Effects of Human Trampling on Populations of Soil Fauna in the McMurdo Dry Valleys, Antarctica - EDWARD AYRES; JOHNSON N. NKEM; DIANA H. WALL; BYRON J. ADAMS; J. E. BARRETT; EMMA J. BROOS; ANDREW N. PARSONS; LAURA E. POWERS; BREANA L. SIMMONS; ROSS A. VIRGINIA (Conservation Biology, 2008)
Antarctic ecosystems are often considered nearly pristine because levels of anthropogenic disturbance are extremely low there. Nevertheless, over recent decades there has been a rapid increase in the number of people, researchers and tourists, visiting Antarctica. We evaluated, over 10 years, the direct impact of foot traffic on the abundance of soil animals and soil properties in Taylor Valley within the McMurdo Dry Valleys region of Antarctica. We compared soils from minimally disturbed areas with soils from nearby paths that received intermediate and high levels of human foot traffic (i.e., up to approximately 80 passes per year). The nematodes Scottnema lindsayae and Eudorylaimus sp. were the most commonly found animal species, whereas rotifers and tardigrades were found only occasionally. On the highly trampled footpaths, abundance of S. lindsayae and Eudorylaimus sp. was up to 52 and 76% lower, respectively, than in untrampled areas. Moreover, reduction in S. lindsayae abundance was more pronounced after 10 years than 2 years and in the surface soil than in the deeper soil, presumably because of the longer period of disturbance and the greater level of physical disturbance experienced by the surface soil. The ratio of living to dead Eudorylaimus sp. also declined with increased trampling intensity, which is indicative of increased mortality or reduced fecundity. At one site there was evidence that high levels of trampling reduced soil CO 2 fluxes, which is related to total biological activity in the soil. Our results show that even low levels of human traffic can significantly affect soil biota in this ecosystem and may alter ecosystem processes, such as carbon cycling. Consequently, management and conservation plans for Antarctic soils should consider the high sensitivity of soil fauna to physical disturbance as human presence in this ecosystem increases.

Wind dispersal of soil invertebrates in the McMurdo Dry Valleys, Antarctica - Johnson N. Nkem; Diana H. Wall; Ross A. Virginia; John E. Barrett; Emma J. Broos; Dorota L. Porazinska; Byron J. Adams (Polar Biology, 2006)

Antidepressants preferentially enhance habituation to novelty in the olfactory bulbectomized rat - Adam Mar; Emma Spreekmeester; Joseph Rochford (Psychopharmacology, 2000)